Pengaruh Motivasi Belajar dan Minat Belajar Terhadap Partisipasi Belajar Pada Mata Pelajaran Ekonomi di SMAS Laboratorium Undiksha Singaraja - Ayuni, Komang Artha Tri; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research has a goal, namely to determine the effect of learning motivation and interest in learning on learning participation in economics subjects at SMA Undiksha Singaraja Laboratory. This research uses a causal type of research. The population in this study were all IIS students at SMA Undiksha Singaraja Laboratory, as many as 60 students, namely 16 X IIS students, 21 IIS class XI students, and 23 students, so the total number of students was 60 students. For that research, all IIS class students were taken. The method of data collection used was a questionnaire; the data analysis technique used was multiple linear regression analysis, and the hypothesis tests used were t test, F test, and coefficient of determination using SPSS version 24. The results of this study indicate that there is a partial effect. Simultaneous learning motivation and interest in learning towards learning participation in economics subjects at SMA Undiksha Singaraja Laboratory.